Evaluation of Athletic Identity in Elite Fencers - Yusuf Barsbuğa (Türk Spor ve Egzersiz Dergisi, 2021)
The objective of the research was to analyze and comment on the sportive identities of the star, young and great athletes actively participated in competitions in our country, became involved among the first 16 athletes in formal classifications (in their own categories) of Turkey Fencing Federation between 2016-2017, and attended in the Big National Team Camp held in the county Antalya/Alanya between the dates of 18-29/8/2016 and the Star-Young Europe Championship Preparation Camp held in the province Ankara between the dates of 18-26/2/2017. The research group consisted of 64 athletes invited to the relevant national team camps in the 2016-2017 season. Based on the survey model, within the relevant study, Athletic Identity Scale which was developed by Brewer and Cornelius (2001), and also validated and made reliable in Turkish by Çetinkaya (2015), was used. In evaluation of data and estimation of values, the SPSS 16.0 statistical package program was utilized. Data was summarized with averages and standard deviations. Since data showed a normal distribution, independence group t-test for pair comparisons, One Way Variance Analysis (anova) for multiple comparisons were preferred. In this study, scale reliability coefficient was calculated as .74. The significance level was regarded as 0.05 in this study. As a result of the research; it was concluded that there were no significant differences in the average points from the Athletic Identity Scale in accordance with the gender variable; there was a significant difference in favour of the participants, aged 15-18, graduating from high school and below in accordance with the age and education background variable among 64 athletes invited to the relevant national team camps in the 2016-2017 season.